Supply Chain and Delivery of Antimicrobial Drugs in Smallholder Livestock Production Systems in Uganda - Dione, Michel Mainack; Amia, Winfred Christine; Ejobi, Francis; Ouma, Emily Awuor; Wieland, Barbara (Frontiers in Veterinary Science, 2021)
This study assessed the veterinary drug supply chain in Uganda, the constraints faced by the actors, and how the challenges influence the use of antimicrobial (AMs) by livestock farmers. We carried out stakeholder consultation workshops, key informant interviews and a Knowledge Attitude and Practices (KAP) survey with actors of the veterinary drug supply chain. We also profiled drugs stored in 23 urban and peri-urban drug shops in Lira and Mukono districts to record the commonly sold drugs. The veterinary drug supply chain is complex with several actors involved including wholesalers, retailers, Animal Health Service Providers (AHSP) and farmers. Nearly ninety per cent of drug retailers and veterinary practitioners did not receive specialized training in veterinary medicine, and most of veterinary practitioners have been in the drug business market for more than 10 years. Antibiotics and anti-helminthics were the most stocked drugs by retailers, with antibiotics ranking highest in terms of contribution to financial profits. Antibiotics accounted for 33% of annual profit. The choice of a drug by veterinary practitioners was mainly informed by past success with efficacy of the drug, and financial capacity of the client (the farmer) to meet the cost of treatment. Many veterinary practitioners were not conversant with veterinary drug policies of the country, with Mukono having a higher number (72%,) compared to Lira (37%). Veterinary practitioners from Lira district compared to Mukono and those mainly serving small scale farmers relative to large scale smallholders were more knowledgeable about antibiotics and AMR. Several supply chain constraints were identified as potential drivers of misuse of antibiotics that could contribute to AMR. These included low level of education of supply chain actors, particularly drug retailers, poor handling of drugs at purchase and administration practices, low enforcement of policy and regulations, and lack of awareness of stakeholders about policies that regulate drug use. Thus, future interventions to reduce misuse of AM drugs in livestock production systems in Uganda such as capacity building, should also target veterinary input suppliers, and deliberately involve a strong policy advocacy component.